(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The purpose of this study was to determine the efficiency of a cognitive-behavioral counselling programme in lowering symptoms of exam anxiety and enhancing academic self-efficacy in a sample of middle school students from the Thi Qar governorate. The sample consisted of (40) pupils who were selected from (90) fifth-grade students attending preparatory schools for boys in Suq Al-Shuyukh (Karma School and the El-Shohada School), on the basis of their high test anxiety scores, they were divided into two groups of similar size, chronological age, and test anxiety score, the experimental group consisted of twenty (20) students who participated in the Cognitive-Behavioral Counseling Program, while the control group consisted of twenty (20) students who did not receive any form of guiding intervention other than the administration of research measures (pre-measurement, posterior, deferred). The study instruments included an exam anxiety scale and an academic self-efficacy scale, in addition to the cognitive-behavioral treatment programme consisting of which consisted of (11) counseling. The semi-experimental method was employed, and the data were analysed using proper statistical methods, the study yielded the following results: a decrease in the level of exam anxiety among the members of the experimental group after the completion of the application of the extension program (post- measurement), A comparison of the experimental and control groups’ post-measurement findings revealed that the experimental group performed better in terms of examination anxiety than the control group. The academic self-efficacy of the experimental sample exhibited significant variations between pre- and post-measurement, and the outcomes supported the use of post-measurement, comparing the postponed measuring results of the experimental and control groups revealed that members of the experimental group performed better in terms of reducing exam anxiety and increasing self-efficacy than members of the control group. The researcher gave a series of recommendations and proposals that came from the findings of this study, notably the design of counselling programmes by school counsellors to reduce exam anxiety, increase academic self-efficacy, and foster motivation and desire to learn